Pengaruh Disiplin Kerja, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Bagian Produksi PT. Karya Mina Putra Divisi Kayu Rembang - Mujib, Abdul; Dewi, Dian Ayu Liana (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to prove and explain the effect of work discipline, work motivation, workenvironment on the performance of production employees of PT Karya Mina Putra RembangWood Division. The population used consisted of 217 employees of the productiondepartment of PT Karya Mina Putra Rembang Wood Division. The sample selectiontechnique used accidental sampling with the determination of sample size using the slovinformula obtained 68 samples. Data collection through questionnaire survey. Data analysisusing multiple linear regression. The results of this study indicate that work discipline has anegative and insignificant effect on employee performance, work motivation has a positiveand insignificant effect on employee performance, while the work environment has asignificant positive effect on employee performance. The adjusted R square value is 0.215, itmeans that 21.5% of variations in employee performance can be explained by variations inthe three independent variables, namely work discipline, work motivation and workenvironment, while the remaining 78.5% is explained by other factors not examined in thisstudy